KESIAPAN GURU SEKOLAH DASAR DALAM PENGGUNAAN MODUL AJAR PADA PEMBELAJARAN IPAS BERBASIS KURIKULUM MERDEKA - Ilham Arwanda Nugraha; Tia Ananda Putri; Nabila Elgha Gaharuni; Muhammad Imaduddin (STKIP Subang, 2026)
A learning module is an important teaching tool for supporting the Merdeka Learning Curriculum, particularly for IPAS, as it emphasizes meaningful, student-centered, learning experiences. This study aims to investigate and describe teachers’ readiness to use the learning module for IPAS teaching within the context of the curriculum. A qualitative descriptive method was employed for the study, with data collected through semi-structured interviews with a third-grade teacher at Sugihwaras 1 elementary school. The data were analyzed through the stage of reduction, presentation, and drawing conclusions. The results revealed that the teachers were well prepared to use the learning modules. This preparedness was demonstrated through their understanding of the concept of the learning module, their ability to design learning activities based on CP, TP and ATP, and their participation in training on the development of learning modules. In practice, teachers implement PBL and PjBL models by utilizing digital learning media such as PowerPoint presentations and educational videos. Teachers also integrated local wisdom and current issues to support more contextualized learning. However, challenges remain in the form of limited learning resources and adapting learning to the diverse characteristics of students. These findings demonstrate that the success of implementing the learning modules is influenced not only by teacher preparedness, but also by adequate support and a conducive learning environment. Therefore, support and continuous training are needed to optimize the implementation of learning modules in the Merdeka Learning Curriculum, particularly for IPAS.